Uncoupling of reactive oxygen species accumulation and defence signalling in the metal hyperaccumulator plant Noccaea caerulescens - Fones, H; Eyles, C; Bennett, M; Smith, J; Preston, G (2013)
The metal hyperaccumulator plant Noccaea caerulescens is protected from disease by the accumulation of high concentrations of metals in its aerial tissues, which are toxic to many pathogens. As these metals can lead to the production of damaging reactive oxygen species (ROS), metal hyperaccumulator plants have developed highly effective ROS tolerance mechanisms, which might quench ROS-based signals. We therefore investigated whether metal accumulation alters defence signalling via ROS in this plant. We studied the effect of zinc (Zn) accumulation by N. caerulescens on pathogen-induced ROS production, salicylic acid accumulation and downstream defence responses, such as callose deposition and pathogenesis-related (PR) gene expression, to the bacterial pathogen Pseudomonas syringae pv. maculicola. The accumulation of Zn caused increased superoxide production in N. caerulescens, but inoculation with P. syringae did not elicit the defensive oxidative burst typical of most plants. Defences dependent on signalling through ROS (callose and PR gene expression) were also modified or absent in N. caerulescens, whereas salicylic acid production in response to infection was retained. These observations suggest that metal hyperaccumulation is incompatible with defence signalling through ROS and that, as metal hyperaccumulation became effective as a form of elemental defence, normal defence responses became progressively uncoupled from ROS signalling in N. caerulescens. © 2013 The Authors © 2013 New Phytologist Trust.